2018
DOI: 10.1155/2018/8047610
|View full text |Cite
|
Sign up to set email alerts
|

Role of Muramyl Dipeptide in Lipopolysaccharide-Mediated Biological Activity and Osteoclast Activity

Abstract: Lipopolysaccharide (LPS) is an endotoxin and bacterial cell wall component that is capable of inducing inflammation and immunological activity. Muramyl dipeptide (MDP), the minimal essential structural unit responsible for the immunological activity of peptidoglycans, is another inflammation-inducing molecule that is ubiquitously expressed by bacteria. Several studies have shown that inflammation-related biological activities were synergistically induced by interactions between LPS and MDP. MDP synergistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 110 publications
0
6
0
1
Order By: Relevance
“…LPS induces RANKL expression from osteoblasts and production of proinflammatory cytokines, such as TNF-α and IL-1, from macrophages and other cells ( 37 ). It has been reported that periodontal ligament cells also express numerous types of proinflammatory cytokines to regulate osteoclastogenesis by LPS ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…LPS induces RANKL expression from osteoblasts and production of proinflammatory cytokines, such as TNF-α and IL-1, from macrophages and other cells ( 37 ). It has been reported that periodontal ligament cells also express numerous types of proinflammatory cytokines to regulate osteoclastogenesis by LPS ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since this lack of effect was independent of plasma-derived factors, it has been suggested that a cellular or cell-derived component from the blood is responsible for the inhibition of MDP in whole blood [19]. Furthermore, although MDP alone cannot induce immunoglobulin production [20], it is able to enhance expression of cell adhesion molecules and cytokines [14]. Moreover, several studies show increased production of proinflammatory cytokines upon MDP stimulation in vitro, also in synergy with other stimuli, which seem to depend on species and cell types used [14,19,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This activates transcription factors such as nuclear factor kappa B (NF-κB), activator protein-1 (AP1) and NFATc1, which are the subsequent genes of TRAF6, resulting in activation of p38, JNK and extracellular-signal regulated kinases (ERK). Activation is carried out at the protein level through phosphorylation processes including mitogen-activated protein kinases (MAPKs) and Phosphatidyl-inositol-3-kinase (PI3K)/Akt pathway 60,61 . Many studies have revealed that MAPKs can be stimulated by RANKL stimulation and are associated with osteoclastogenesis [62][63][64][65] .…”
Section: Discussionmentioning
confidence: 99%